2016
DOI: 10.1021/jacs.6b09829
|View full text |Cite
|
Sign up to set email alerts
|

Defining Noncovalent Ubiquitin Homodimer Interfacial Interactions through Comparisons with Covalently Linked Diubiquitin

Abstract: Covalently linked diubiquitin (diUbq) is known to adopt specific interfacial interactions owing to steric hindrance induced by the covalent tether. K48-linked diUbq preferentially forms hydrophobic interfacial interactions between the two I44 faces under physiological conditions, whereas K63-linked diUbq preferentially forms electrostatic interfacial interactions. Here, we show using collision-induced unfolding ion mobility-mass spectrometry that the recently reported noncovalent dimer of ubiquitin exhibits st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 28 publications
6
28
0
Order By: Relevance
“…Overall, our analysis revealed the involvement of many charged residues in the Ub-Ub interface and suggests that K63-Ub2 prefer electrostatic interfacial contacts, being hindered by steric constraints to interact via the common I44/I36 hydrophobic patches, in line with previous reports 65 .…”
Section: Validation and Analysis Of The Ub-ub Interfacessupporting
confidence: 91%
“…Overall, our analysis revealed the involvement of many charged residues in the Ub-Ub interface and suggests that K63-Ub2 prefer electrostatic interfacial contacts, being hindered by steric constraints to interact via the common I44/I36 hydrophobic patches, in line with previous reports 65 .…”
Section: Validation and Analysis Of The Ub-ub Interfacessupporting
confidence: 91%
“…Further evidence supporting the proposed mechanism for water‐mediated formation of the Ubq dimer comes from studies on the CIU of the noncovalent dimer and the K‐6, K‐11, K‐48, and K‐63 covalent dimers. The K‐48 dimer is known to contain strong interactions involving the I‐44 hydrophobic patch, and the CIU heat maps for the K‐48 and noncovalent dimer are almost identical (Wagner & Russell, 2016).…”
Section: Water‐mediated Dimerization Of Ubqmentioning
confidence: 99%
“…Similarities between the unfolding pathways of noncovalent and K48‐linked ubiquitin dimers ( B and E , respectively) suggest the noncovalent dimer adopts similar subunit interfacial interactions to the K48‐linked covalent ubiquitin dimer. CIU heatmaps are reproduced from references Wagner and Russell (2016); Wagner et al (2017). CIU, collision‐induced unfolding; NMR, nuclear magnetic resonance.…”
Section: Stabilities Of Gas‐phase Protein Ions: Ciumentioning
confidence: 99%
“…The noncovalent association of Ub monomers was recently detected using paramagnetic relaxation enhancement (PRE) NMR studies, which suggested that the dimer structure of Ub resembled K48 linked Ub 2 . Another report using collision‐induced unfolding ion mobility‐mass spectrometry showed that the noncovalent Ub 2 exhibited similar interfacial interactions and structural stability as K48 linked Ub 2 . However, recently reported crystal structure of Ub monomers showed an arrangement of four subunits in the asymmetric crystal unit resembling the structure of K11 linked Ub 2 .…”
Section: Introductionmentioning
confidence: 99%